POTENSI KERJA SAMA SISTER CITY KOTA MAGELANG DENGAN KOTA BREDA (BELANDA) - Yun Arifatul Fatimah; Eny Boedi Oerbawati; Retno Rusdjijati; Oesman Raliby; Awaluddin Setya Aji; Doddy Ardjono; Andreas Pandiangan; Arizal Arizal; Agus Setyowidodo (Badan Perencanaan Pembangunan Daerah Kota Magelang, 2020)
Sister city is a formal understanding agreement made between two cities, which have something in common, which is set forth in a memorandum of understanding, to establish cooperation in various fields. Judging from past history, demographic conditions, social culture, and economic performance, Magelang Municipality and Breda Municipality have many similarities, namely as a City of Military Education, City of Students and Culture, City of Industry and City of Services. This similarity raises the potential for cooperation in the sister city program with the main objective of sustainable development of human, economic, socio-cultural and environmental resources. To achieve these objectives, there are 5 (five) priority programs proposed, namely urban planning, management and construction, vocational education in tourism, water and renewable energy engineering, promotion of cities and regions, and military education cooperation. Some strategic steps, starting from planning and implementation, and the control mechanism and sister city scheme are proposed in this paper as consideration for Magelang Municipality in implementing the program.